2014
DOI: 10.1542/peds.2013-3049
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infection Among Children Across Diverse US Geographic Locations

Abstract: OBJECTIVE: Little is known about the epidemiology of Clostridium difficile infection (CDI) among children, particularly children ≤3 years of age in whom colonization is common but pathogenicity uncertain. We sought to describe pediatric CDI incidence, clinical presentation, and outcomes across age groups. METHODS: Data from an active population- and laboratory-based CDI surveillance in 10 US geographic areas during 2010–2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
100
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 29 publications
8
100
0
4
Order By: Relevance
“…For example, we previously reported antibiotic exposure in the previous 30 days among 26% of children with CA-CDI (compared to 88% of children with hospital-onset health care facility-associated [HO-HCFA] CDI), and Tschudin-Sutter et al reported antibiotic exposure in the previous 30 days among 42% of children with CA-CDI (compared to 76% of children with HCFA-CDI). Furthermore, we previously reported that CA-CDI is the most common type of CDI in a pediatric cohort (11), and other population-based studies support this; CA-CDI accounted for 60% to 80% of CDIs, depending on age, in a U.S. surveillance study (24) and for 75% of cases in a population-based study in Minnesota (25). Thus, because of the predominance of CA-CDI in children and the relatively infrequent rate of antibiotic exposure preceding CA-CDI in children, this may account for the favorable susceptibility profile among our pediatric isolates.…”
Section: Discussionmentioning
confidence: 58%
“…For example, we previously reported antibiotic exposure in the previous 30 days among 26% of children with CA-CDI (compared to 88% of children with hospital-onset health care facility-associated [HO-HCFA] CDI), and Tschudin-Sutter et al reported antibiotic exposure in the previous 30 days among 42% of children with CA-CDI (compared to 76% of children with HCFA-CDI). Furthermore, we previously reported that CA-CDI is the most common type of CDI in a pediatric cohort (11), and other population-based studies support this; CA-CDI accounted for 60% to 80% of CDIs, depending on age, in a U.S. surveillance study (24) and for 75% of cases in a population-based study in Minnesota (25). Thus, because of the predominance of CA-CDI in children and the relatively infrequent rate of antibiotic exposure preceding CA-CDI in children, this may account for the favorable susceptibility profile among our pediatric isolates.…”
Section: Discussionmentioning
confidence: 58%
“…Historically, outpatient populations have been thought to be at lower risk of CDI. In a laboratory-based surveillance study by Wendt et al, the rate of C. difficile detection from testing of children in the community was 71% (26). However, this study and others have not correlated the positive laboratory findings with clinical data, making the link between a positive test and the causality of disease unclear (5).…”
mentioning
confidence: 65%
“…The prevalence of CDI in children is increasing (17), with the highest CDI incidence among children 1 to 4 y of age (18). Recurrence of CDI can occur in 20-30% after initial infection, with the frequency of recurrence rising further after subsequent infections (19)(20)(21).…”
Section: Fmt For Recurrent CDI In Childrenmentioning
confidence: 99%